Dana Desa dan Status Desa di Provinsi Jawa Tengah - Yulitasari Yulitasari; Wido Prananing Tyas (P4W LPPM IPB, 2020)
Village Funds and Village Status in Central Java Province Year 2019 is the fifth year of implementation of village fund in Indonesia. At the beginning of its implementation in 2015, village funds were budgeted at IDR 20.8 trillion, which has increased to 3.5 times and reaching about IDR 70 trillion in 2019. This research is aimed to describe village funds and villages status in Central Java Province and the relationship between them. Data to be used are secondary data consisting of village funds and village status according to IDM year 2018 and 2019 in Central Java Province. The analyses used in this research are descriptive statistics and simple regression. Results show that village funds in Central Java Province increase about 14.7% in 2019 and there is an increase in the aggregate of village status. Regression analysis showed that changes in the amount of village funds did not significantly affect the change of village status in Central Java Province.